ASSESSING THE IMPACT OF AGRICULTURAL PRACTICES AND PESTICIDE USAGE ON THE WATER QUALITY OF KUTTANAD AGROECOSYSTEM - Aswathy Joshy, Niladevi K.N and Shirley Thomas (DISCOURSE Xaverian Research Journal, 2018)
Alappuzha (Kuttanad) referred to as the Venice of the East is a part of Vembanad –Kol wetland system which is also one of the important Ramsar site in India. This novel ecosystem is currently under threat due to various anthropogenic activities including intensive agricultural practices. Considering the ecological and economic significance of Kuttanad, a study was undertaken to analyze the pollution status of the water bodies of this region. Two different sites of Kuttanad wetland system were selected for the study. One was highly influenced by the discharge of water from paddy fields (test site) and another with less intense agricultural activities (control site). The study has revealed that the organophosphorous pesticide chlorpyrifos is present in the test sample at an alarming concentration of 10.18ug/L. The study on different water quality parameters has revealed a considerable increase in the levels of alkalinity, nitrate, phosphate and ammonia in the test sample. istological studies conducted on Villorita sp. were also in support of the heavy pesticide pollutionin the water bodies of Kuttanad region. The present study attempts to unveil the pollution status of this significant Ramsar site so that better eco-restoration strategies could be developed for its conservation and sustainable use.